Toxicity and bioavailability of mercury in spiked sediments on Hyalella curvispina Shoemaker, 1942 - Peluso, María Leticia (2013)
Mercury is a non-essential toxic heavy metal often found in bottom freshwater sediments. The aim of the present study was to evaluate the influence of the organic matter (OM) on the toxicity and bioavailability of mercury in sediment samples on the amphipod Hyalella curvispina, assessing survival and growth under chronic exposure. Species sensitivity in water-only tests was LC-50 of 96 h 0.025 mg/L. Results indicate that sediments with OM did not induce lethality under concentrations of mercury up to 10 mg/kg dw. On the contrary, exposed organisms to sediments without OM were significantly affected at half of that metal concentration. Sublethal effects were evident at 3 mg/kg. Presence and proportion of OM in sediment is clearly influencing mercury bioavailability, affecting toxicity in a different level according to the end point being assessed.